2021
DOI: 10.1542/peds.2020-042507
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes in Young Children Following Pertussis Vaccination During Pregnancy

Abstract: BACKGROUND AND OBJECTIVES: Maternal immunization with tetanus, diphtheria, and acellular pertussis vaccine (Tdap) is routinely recommended in many countries as a strategy to protect young infants against severe pertussis infection; few studies have assessed whether prenatal exposure to the vaccine is associated with any longer-term adverse health effects in children. We evaluated the long-term safety of exposure to Tdap vaccination during pregnancy.METHODS: Population-based retrospective cohort study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In particular, Tdap vaccination in pregnancy had no effect on the incidence of autism spectrum disorder [ 54 ], attention-deficit hyperactivity disorder [ 55 ], infant growth problems [ 59 ], or hospitalization and death rates in the first 6 months of life [ 68 ]. Additionally, one study showed an inverse association of Tdap vaccination in pregnancy with infant upper respiratory infection, gastrointestinal infection, and urgent/inpatient healthcare use [ 62 ], and, in another study, the incidence of respiratory hospitalization was shown to be higher in infants without Tdap vaccination in pregnancy [ 68 ]. No cases of pertussis illness occurred in mothers or infants according to the study reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Tdap vaccination in pregnancy had no effect on the incidence of autism spectrum disorder [ 54 ], attention-deficit hyperactivity disorder [ 55 ], infant growth problems [ 59 ], or hospitalization and death rates in the first 6 months of life [ 68 ]. Additionally, one study showed an inverse association of Tdap vaccination in pregnancy with infant upper respiratory infection, gastrointestinal infection, and urgent/inpatient healthcare use [ 62 ], and, in another study, the incidence of respiratory hospitalization was shown to be higher in infants without Tdap vaccination in pregnancy [ 68 ]. No cases of pertussis illness occurred in mothers or infants according to the study reports.…”
Section: Resultsmentioning
confidence: 99%
“…These VE data support the many national recommendations for Tdap vaccination in pregnancy to prevent hospitalization and death from pertussis in young infants. Additionally, one study showed that infants without Tdap vaccination in pregnancy were more likely to be hospitalized due to respiratory symptoms [ 68 ], and another showed an inverse relationship between Tdap vaccination during pregnancy and infant upper respiratory tract infections [ 62 ]. The impact of vaccination with Adacel and Adacel-Polio during pregnancy continues through the first year of life, even after the infant’s primary DTaP vaccination series.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal pertussis immunization is an effective intervention for mitigating the burden of severe pertussis illness in young infants, with estimates of vaccine effectiveness ranging from 36 to 90% in several studies [26][27][28][29][30][31][32][33][34]. Further, antenatal Tdap immunization is safe, with multiple studies finding no association between vaccination and adverse fetal or neonatal outcomes [12,[34][35][36][37]]. Yet, despite supportive evidence, several studies have documented suboptimal uptake of maternal pertussis immunization [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Infertility was a major concern, and it is important for governments and professional associations to quickly address misinformation circulating online and on social media with scientific evidence. Many respondents were concerned with fetal growth and development, and there are now many studies available for other vaccines showing that vaccination during pregnancy is not associated with long-term adverse health consequences in children [28][29][30][31]. These should be shared widely and used in knowledge dissemination campaigns with HCPs and our communities.…”
Section: Discussionmentioning
confidence: 99%